Broadband fiber-chip zero-order surface grating coupler with 0.4 dB efficiency. - Sánchez-Postigo, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Luque-González, José Manuel; Molina-Fernández, Íñigo; Cheben, Pavel; Alonso-Ramos, Carlos A.; Halir, Robert; Schmid, Jens H.; Ortega-Moñux, Alejandro (Optica Publishing Group, 2016)
Surface grating couplers enable efficient coupling of light between optical fibers and nanophotonic waveguides. However, in conventional grating couplers, the radiation angle is intrinsically wavelength dependent, thereby limiting their operation bandwidth. In this Letter, we present a zero-order surface grating coupler in silicon-on-insulator which overcomes this limitation by operating in the subwavelength regime. By engineering the effective refractive index of the grating region, both high coupling efficiency and broadband operation bandwidth are achieved. The grating is assisted by a silicon prism on top of the waveguide, which favors upward radiation and minimizes power losses to substrate. Using a linear apodization, our design achieves a coupling efficiency of 91% (−0.41 dB) and a 1-dB bandwidth of 126 nm.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/13362
Keywords: Redes de banda ancha; Nanofotónica; Silicon photonics; Surface grating couplers; Subwavelength grating metametarials